2020
DOI: 10.1186/s13063-020-4227-1
|View full text |Cite
|
Sign up to set email alerts
|

Perceived barriers to randomised controlled trials in breast reconstruction: obstacle to trial initiation or opportunity to resolve? A qualitative study

Abstract: Background: Implant-based breast reconstruction (IBBR) is the most commonly performed breast reconstruction technique worldwide but the technique is evolving rapidly. High-quality evidence is needed to support practice. Randomised controlled trials (RCTs) provide the best evidence but can be challenging to conduct. iBRA is a four-phased study which aimed to inform the feasibility, design and conduct of an RCT in IBBR. In phase 3, the randomisation acceptability study, an electronic survey and qualitative inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 52 publications
0
18
0
Order By: Relevance
“…Ideally, a well designed pragmatic RCT is required to establish definitively which reconstructive technique is most clinically and cost effective, and provides the best outcomes for patients. The iBRA RCT acceptability study has suggested that a trial may be feasible 45 and the Best-BRA external pilot study (ISRCTN10081873) will determine whether it is possible to recruit patients to an RCT comparing prepectoral and subpectoral techniques before progressing to a definitive large-scale trial. Similar RCTs are underway in Europe, and will generate much needed evidence to support practice and policy.…”
Section: Discussionmentioning
confidence: 99%
“…Ideally, a well designed pragmatic RCT is required to establish definitively which reconstructive technique is most clinically and cost effective, and provides the best outcomes for patients. The iBRA RCT acceptability study has suggested that a trial may be feasible 45 and the Best-BRA external pilot study (ISRCTN10081873) will determine whether it is possible to recruit patients to an RCT comparing prepectoral and subpectoral techniques before progressing to a definitive large-scale trial. Similar RCTs are underway in Europe, and will generate much needed evidence to support practice and policy.…”
Section: Discussionmentioning
confidence: 99%
“…The QRI will be implemented in two key phases—phase 1, in which sources of recruitment difficulties are rapidly investigated to inform the delivery in phase 2 of tailored interventions to optimise recruitment and informed consent. This will be supplemented with upfront pre-emptive recruitment training in study set up, tailored to anticipated issues and informed by previous QRIs 42 52 55 68 69…”
Section: Methodsmentioning
confidence: 99%
“…53 While the majority of respondents felt that an appropriately designed RCT in IBBR may be possible, 51 qualitative interviews with key stakeholders identified a number of barriers to the successful conduct of a future trial. 52 These included limited understanding of a pragmatic study design and the role of randomisation in minimising bias, issues around clinician equipoise and aspects of surgical culture not being supportive of RCTs.…”
Section: Open Accessmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, there is no consensus regarding how these outcomes should be evaluated. There are few studies providing high-quality evidence supporting the use of different techniques for breast reconstruction and it is well-known that it is challenging to conduct randomized clinical trials (RCTs) in breast reconstruction, mainly due to patients' and surgeons' preferences leading to recruitment difficulties 2 . Consequently, there are few RCTs comparing quality of life in different breast reconstruction techniques [3][4][5] .…”
Section: Introductionmentioning
confidence: 99%